BLOCK SYSTEM CURRICULUM MANAGEMENT AND IMPLEMENTATION OF PROJECT-BASED LEARNING TO IMPROVE THE SKILLS COMPETENCY OF STUDENTS AT SMK NEGERI 1 SANGATTA UTARA - Paridah; A Azainil; M Bahzar; Nurlaili Nurlaili; K Khairuddin; U Haryaka (Pena Cendekia Insani, 2026)
Improvement competence skill student School Intermediate Vocational (SMK) becomes demands it is important that graduates capable fulfil the needs of the business world and the industrial world. However, there are still there is gap between competence vocational school graduates and needs industry so that required innovation in management curriculum. Research This aim analyze management curriculum system blocks and implementation Project Based Learning (PjBL) in increase competence skill students at State Vocational School 1 North Sangatta. Research use approach qualitative with design studies case. Data collection was carried out through interviews, observations, and documentation with informant head school, deputy principal school field curriculum, head of expertise program, and teachers. Data analysis was carried out through data reduction, data presentation, and data extraction conclusion with validity test through triangulation. Research results show that management curriculum system integrated block with PjBL implemented through function planning, organizing, implementing and monitoring as well as supported by teacher competence, facilities infrastructure and partnerships industry. Conclusion study shows that implementation system blocks and PjBL capable increase competence skill as well as readiness Work student.